Response of the seated human body to whole-body vertical vibration: biodynamic responses to sinusoidal and random vibration - Zhou, Zhen; Griffin, Michael J. (Ergonomics, 2014)
The dependence of biodynamic responses of the seated human body on the frequency, magnitude and waveform of vertical vibration has been studied in 20 males and 20 females. With sinusoidal vibration (13 frequencies from 1 to 16 Hz) at five magnitudes (0.1-1.6 ms − 2 r.m.s.) and with random vibration (1-16 Hz) at the same magnitudes, the apparent mass of the body was similar with random and sinusoidal vibration of the same overall magnitude. With increasing magnitude of vibration, the stiffness and damping of a model fitted to the apparent mass reduced and the resonance frequency decreased (from 6.5 to 4.5 Hz). Male and female subjects had similar apparent mass (after adjusting for subject weight) and a similar principal resonance frequency with both random and sinusoidal vibration. The change in biodynamic response with increasing vibration magnitude depends on the frequency of the vibration excitation, but is similar with sinusoidal and random excitation. Practitioner Summary: Biodynamic responses (e.g. body resonances) influence vibration discomfort and are studied with random vibration, whereas psychological responses to vibration are studied with sinusoidal vibration. Vibration in transport includes both random and sinusoidal vibration. This study shows the frequency-dependence and magnitude-dependence of biodynamic responses are similar with random and sinusoidal vibration.